Agrarian Justice in Aceh Customary Law: A Study of Customary Land in Aceh Besar - Novianti, Leny (Jurnal Ilmiah Teunuleh, 2024)
Agrarian justice in Indonesia does not only depend on the formal legal framework, but is also strongly influenced by the existence and recognition of the customary law system, especially in indigenous communities such as in Aceh. This research aims to examine agrarian justice in the perspective of Acehnese customary law through a case study of customary land in Aceh Besar District. Using a descriptive qualitative approach and field study methods as well as in-depth interviews, this research highlights the role of customary law in regulating ownership, distribution and resolution of agrarian conflicts. The findings show that indigenous communities in Aceh Besar have customary land management mechanisms based on the principles of deliberation, collective justice and spiritual values, but often face unclear legal status and lack of administrative recognition from the state. Agrarian conflicts often occur due to overlapping claims between indigenous peoples and formal control by outsiders. This research recommends strengthening the synergy between customary law and national law in the form of contextual agrarian policies, participatory legalization of customary land, and protection of collective rights of indigenous peoples as a step towards sustainable agrarian justice in Aceh.